I found you : a novel - Jewell, Lisa (Atria Books, 2017)
In a windswept British seaside town, single mom Alice Lake finds a man sitting on the beach outside her house. He has no name, no jacket, and no idea how he got there. Against her better judgment, she invites him inside. Meanwhile, in a suburb of London, twenty-one-year-old Lily Monrose has only been married for three weeks. When her new husband fails to come home from work one night she is left stranded in a new country where she knows no one. Then the police tell her that her husband never existed. Twenty-three years earlier, Gray and Kirsty are teenagers on a summer holiday with their parents. Their annual trip to the quaint seaside town is passing by uneventfully, until an enigmatic young man starts paying extra attention to Kirsty. Something about him makes Gray uncomfortable, and it's not just that he's playing the role of protective older brother.--